2023
DOI: 10.1002/1878-0261.13453
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular LGALS3BP: a potential disease marker and actionable target for antibody–drug conjugate therapy in glioblastoma

Abstract: Glioblastoma multiforme (GBM) is a lethal disease characterized by an overall survival of about 1 year, making it one of the most aggressive tumours, with very limited therapeutic possibilities. Specific biomarkers for early diagnosis as well as innovative therapeutic strategies are urgently needed to improve the management of this deadly disease. In this work, we demonstrated that vesicular galectin‐3‐binding protein (LGALS3BP), a glycosylated protein overexpressed in a variety of human malignancies, is a pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 59 publications
(97 reference statements)
1
10
0
Order By: Relevance
“…Similar to CYFIP2, whether its expression is favourable or adverse appears to be cancer-dependent, but the majority of research suggests that high expression is associated with unfavourable clinical outcomes [ 38 ]. In cancer, the majority of research has focussed on the secreted versions of LGLAS3BP, with LGALS3BP found in plasma, a proposed biomarker for early detection and overall survival in glioma patients [ 39 , 40 ]. Tissue expression has also been investigated and, as in this study, has been shown to be associated with decreased overall survival [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to CYFIP2, whether its expression is favourable or adverse appears to be cancer-dependent, but the majority of research suggests that high expression is associated with unfavourable clinical outcomes [ 38 ]. In cancer, the majority of research has focussed on the secreted versions of LGLAS3BP, with LGALS3BP found in plasma, a proposed biomarker for early detection and overall survival in glioma patients [ 39 , 40 ]. Tissue expression has also been investigated and, as in this study, has been shown to be associated with decreased overall survival [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the investigations of HSP20 in glioma research is rare. LGALS3BP, namely galectin-3-binding protein, is a glycosylated protein overexpressed in various human tumors and is a potential novel diagnostic biomarker and therapeutic target in GBM deserving further validation [20] . UST encodes uronyl 2-sulfotransferase which transfers sulfate to the 2-position of uronyl residue.…”
Section: Discussionmentioning
confidence: 99%
“…It is a multi-function glycosylated protein, an abundant component of cancer‐derived EVs, and a key regulator of cancer-stroma interactions (reviewed in Capone et al, 2021). It has been described as a biomarker and as a therapeutic target (Dufrusine et al, 2023). Overall, it is a substantially more abundant protein than the Sulf-2 enzyme.…”
Section: Discussionmentioning
confidence: 99%